2013
DOI: 10.1108/jmtm-05-2011-0046
|View full text |Cite
|
Sign up to set email alerts
|

The influence of national level factors on international kaizen transfer

Abstract: The purpose of this research study was to examine the international transfer of kaizen. The central research question was formulated as what national level factors influence the transfer of kaizen? In the study, an inductive case study approach was followed with semi-structured interviews. The study focused on Japanese subsidiaries in the Netherlands. A total of 15 companies participated in the research. Two main factors, not previously identified in the literature, were found: the level of eagerness of employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 68 publications
0
23
1
1
Order By: Relevance
“…Also, the use of practices, tools and/or techniques allows the development of continuous improvement among all members of the organization. Some studies have shown that quality tools such as Pareto charts, check sheets, cause-effect diagrams, and brainstorming are the most widely used (Alvarado and Pumisacho, 2017; Yokozawa and Steenhuis, 2013; Bessant et al , 1994). In this sense, the link to quality management systems as support for daily continuous improvement activities has a positive influence on the organization (Singh and Singh, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, the use of practices, tools and/or techniques allows the development of continuous improvement among all members of the organization. Some studies have shown that quality tools such as Pareto charts, check sheets, cause-effect diagrams, and brainstorming are the most widely used (Alvarado and Pumisacho, 2017; Yokozawa and Steenhuis, 2013; Bessant et al , 1994). In this sense, the link to quality management systems as support for daily continuous improvement activities has a positive influence on the organization (Singh and Singh, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zimmermann and Bollbach (2015) point out China's traditional norms of management, education, and legal systems are cultural barriers to achieve continuous improvement targets. The Netherlands are severally reported as the challenging country for transfer of Kaizen (Yokozawa, Steenhuis & de Bruijn, 2012;Yokozawa & Steenhuis, 2013). In the international transfer of Kaizen, Yokozawa et al (2012) confirms that the appropriate organizational culture is clan culture despite the hierarchical culture.…”
Section: Literature Reviewmentioning
confidence: 85%
“…This study was conducted with the focus on proposing an evaluation model which empowers decision makers to assess their compatibility of organizational culture to Lean culture before any deployment. Literature review revealed that national culture differences influence on Kaizen programs adoption and Lean transfer (Wong, 2007;Yokozawa, et al, 2010;Yokozawa & Steenhuis, 2013;James & Jones, 2014;Wangwacharakul, et al, 2014;Pakdil & Leonard, 2015;Tsao, Rau & Ma, 2015;Zimmermann & Bollbach, 2015). Moreover, some studies examined cultural profile of Lean organization through GLOBE model (House et al, 2004) which the results are in contradictions (Kull et al, 2014;Bortolotti et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings show that there is a positive correlation between the application of Kaizen and culture in relation to the performance of companies in Vietnam, and it is proposed to adapt effectively and flexibly the Kaizen practice to local culture in order to improve performance and achieve a competitive advantage. At the same time, other surveys (Yokozawa, Steenhuis, 2013) confirmed that it is easier to transfer Kaizen to Southeast Asian countries, like Vietnam, than to European countries because the employees are more obedient and disciplined.…”
Section: The Experience In International Kaizen Implementation Transfermentioning
confidence: 96%